Integration of Artificial Intelligence& It’s Practices in Apparel Industry - Dr. Bharati Rathore (International Journal of New Media Studies: International Peer Reviewed Scholarly Indexed Journal, 2023)
AI is being used by manufacturers to automate production processes and reduce the risk of errors. AI-powered robots and machines are being used to increase accuracy, reduce the number of labour hours and even predict when a machine is likely to fail – thus helping to reduce downtime of the production machines. AI can also be used in the fashion and apparel industry to improve product design and optimize the production process.